Fifty years that changed the international status of the Portuguese language - Margarita Correia (Revista de Llengua i Dret - Journal of Language and Law)
This paper’s main objective is to show how the return to democracy by Portugal (1974) and Brazil (1985) accounts for the outstanding development of the Portuguese language over the past fifty years, supporting the idea that the development of a language is closely related to politics, and democratic regimes in particular. To fulfil this objective, the paper presents significant factors that I consider to have been crucial to this dramatic change in the status of the Portuguese language: geopolitical changes, the post-colonial geolinguistic panorama, the growth of education and literacy, the use of Portuguese in international organisations, and economic growth. A further aim is to increase and update general information on the Portuguese language and portray its current global status. The perspective adopted is mainly descriptive; nevertheless, a critical interpretation of the facts will also be present throughout the paper.